INVESTIGATING LEXICAL BUNDLES IN THE CORPORA OF ENGLISH AND INDONESIAN RESEARCH ARTICLES WITH THE SKETCH ENGINE - Susi Yuliawati; Dian Ekawati; Ratna Erika Mawarrani (Fakultas Seni Rupa dan Desain ITB, 2021)
The low publication rate of Indonesian researchers in reputable international journals, particularly in arts and humanities,is caused, among others, by difficulties they faced in producing precise expository texts in English, which are differentfrom texts in Indonesian. The present study examines lexical bundles in the corpora of English and Indonesian researcharticles (RA) on literature and linguistics to describe the similarities and differences of conventionalized phraseology inthe scientific genre of English and Indonesian by using corpus software, namely Sketch Engine. The study focuses onthe frequency, structural and functional characteristics of lexical bundles using a mixed-method research design. TheEnglish corpus comprises 1,351,048 words derived from 124 RA, while the Indonesian corpus consists of 637,910 wordscollected from 124 RA. We found that three-word lexical bundles are more prevalent than four-word lexical bundles inboth corpora. Based on the structural forms, prepositional-based bundles are the most frequent form in English RA, whilenoun-based bundles are the most common form in Indonesian RA. There were no participant-oriented bundles foundin the Indonesian RA corpus in terms of functional classification, whereas the English RA corpus involved more variedfunctional categories of lexical bundles. The findings provide an understanding of phraseological combinations in Englishand Indonesian scientific writing, characterizing disciplinary discourse as well as native and non-native English speakers’rhetorical style, and have pedagogical implications for EAP practitioners.